Gereja Metaverse: Ancaman Serta Peluang Terhadap Misi dan Pertumbuhan Gereja - Toisuta, Jakson; Tankoma, Rudy; Angdry, Teddy; Pardede, Nurmalia (Jurnal Apokalupsis, 2025)
Churches in the virtual digital world, known as metaverse churches, still generate pros and cons. Some groups accept them, while others disagree because metaverse churches are considered incompatible with the word of God. This study aims to provide an analysis of how we, as God's people, should view and interpret the emergence of the metaverse church, not merely as a threat, but also as an opportunity for spreading the church's mission and ministry. The research method used is descriptive qualitative with a library research approach. The primary data sources are various books, scientific journal articles, internet articles, Google Books, seminar materials, and the Bible. This study shows that church ministry and mission through the metaverse church platform can be an open opportunity for church ministry and mission, namely that the metaverse church can be a place or means of worship for those who cannot physically attend a conventional church, a place to become a universal church for all circles, and an option for worship for churches that often experience persecution in the real world